Pengembangan LKPD IPA guided inquiry untuk meningkatkan produk kreativitas peserta didik SMP/MTs - Fitria Sulviana (Jurnal Pendidikan Matematika dan Sains, 2016)
Penelitian ini bertujuan untuk: (1) mengetahui kelayakan lembar kegiatan peserta didik (LKPD) IPA yang dikembangkan dengan pendekatan guided inquiry di SMP/MTs. (2) meningkatkan produk kreativitas peserta didik berupa mapping melalui penggunaan LKPD IPA yang dikembangkan. Penelitian ini merupakan Research and Development (RD) dengan mengacu pada model Borg Gall yang dimodifikasi. Kelayakan produk dinilai oleh seorang ahli materi dan seorang ahli media, tiga pendidik IPA, dan dua teman sejawat. Ujicoba produk dilakukan sebanyak dua kali yaitu ujicoba terbatas dan ujicoba lapangan. Subjek penelitian yaitu peserta didik kelas VIII SMP/MTs.. Hasil penelitian menunjukkan bahwa: (1) LKPD hasil pengembangan dinilai “sangat baik” ditinjau dari aspek materi, aspek penyajian, aspek kebahasaan, dan aspek kegrafikaan, dan (2) terjadi peningkatan produk kreativitas peserta didik berupa mapping dari rerata skor 172,47 naik menjadi 311,06. Hasil tersebut menunjukkan bahwa LKPD IPA dengan topik “Cahaya dalam Kehidupan” layak digunakan untuk meningkatkan produk kreativitas peserta didik berupa mapping.Kata Kunci: LKPD, IPA, pendekatan guided inquiry, produk kreativitas peserta didik, mapping Developing Guided Inquiry Science SAS to Improve Students’ Creativity Product AbstractThe aim of this study was: (1) to determine the feasibility of students’ activity sheet (SAS) which was developed through inquiry approach on science at SMP/MTs, (2) to improve product of students’ creativity in the form of mapping through the use of SAS which was developed. This study was Research and Development (R D) which used Borg Gall’s model. It was modified from ten to seven steps. The assesment of this product was conducted by the judgement from a material expert and a media expert, three science teachers, and two collegues. The subject of this study were students of Year VIII. The product tested twice: preliminary field and main field testing. The preliminary field testing was administered at MTsN Donomulyo Kulon Progo while main field testing was administered at Junior High School of Wates 2 Kulon Progo. The result of the study showed that: (1) the developed SAS was in “very good” category in terms of the materials aspect, the presentation aspect, the language aspect, and the graphic aspect and (2) there was improvement from the products of students’ creativity in the form of mapping from 172.47 to 311.06. The result of the development showed that the SAS of science learning with the topic of “Light in Life” was suitable to be used to improve the product of students’ creativity in the form of mapping.Keywords: SAS, Science, guided inquiry approach, students’ creativity product, mapping